Prototype Smart Greenhouse Untuk Tanaman Aglaonema Dengan Sistem Monitoring Berbasis IoT - Afriantoni Afriantoni; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Internet of Things (IoT) is a concept for exchanging data through the internet with objects that can be controlled remotely. Aglaonema plant is one of the ornamental plants that is much in demand by many as aplant for indoor decoration and terrace houses. It's just that the aglaonema plant to grow nice and beautiful requires a lot of attention. This research designed a system to monitor soil moisture and automatic roof on aglaonema plant through web server and android notifications. The device consists of Arduino Uno, soil moisture sensor, RTC, servo, and limit switch. Checking the soil moisture and opening the roof is done 2 hours in the morning and 2 hours in the afternoon. The roof is opened with a servo, and the limit switch is used to notify if the roof cannot open in time. Monitoring via the web is done using thingspeak and android notifications using IFTTT.Keywords: Monitoring, soil moisture sensor, IoT, Notificaton